ANALISIS PENGANGGARAN DANA BANTUAN OPERASIONAL SEKOLAH DALAM MENINGKATKAN SARANA DAN PRASARANA PERPUSTAKAAN DI SMK AL-JAUHARIYAH - Widiasari; Rahayu, Sri; Terawati, Mira Teram (Jurnal Nusa Akuntansi, 2024)
This study aims to analyze the utilization of School Operational Assistance (BOS) funds in the context of library improvement. School libraries have an important role in improving the quality of education and BOS funds are a source of funding that can be used for it, This research was conducted using descriptive-analytical methods. Data were obtained through surveys, interviews, and documentation studies on schools receiving BOS funding. Research respondents included school principals, library managers, and related teachers. The results showed that the utilization of BOS funds for library improvement is still not optimal. Most schools use the funds to purchase new reference books, update library collections, improve library accessibility, and provide facilities that support learning in the library. There are still several obstacles that hinder the effective use of funds, such as lack of awareness of the importance of library development, knowledge and skills of library managers, and limited budget allocated.